Nontrivial Stable Control Economic Model of Sports Facilities - Kebai Li; Wenjing Zhang; Lifei Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Given that multiple regions have their own development speeds of supply and demand for public sports facilities, a dynamic supply and demand control model of multiple regional public sports facilities is built in this paper. With the range of residents' income increases and the public sports facilities supply investment as the control variables, we established a unified construction controlling means by using the Linear Matrix Inequality approach derived from Lyapunov stability theory. As such, this means guarantees that the systems of public sports facilities in multiple regions with various developments are asymptotically stable; meanwhile, it can lower the difficulty of the control. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3888